Fabrication and Characterization of Single-segmented CoNiP and Multi-segment CoNiP/Au Nanowires - Tu, Le Tuan; Thiem, Luu Van (Communications in Physics, 2014)
This paper represents the fabrication of CoNiP single segment and CoNiP/Au multisegment nanowires. We have fabricated these nanowires by electrodeposition method into polycarbonate templates with a nominal pore diameter about 100 nm. The hystersis loops were measured with the applied magnetic field parallel and perpendicular to the wire axis using a vibrating sample magnetometry (VSM). The structure morphology was observed by Scanning Electron Miroscopy (SEM) and the element composition of CoNiP/Au multisegment nanowires were analyzed by EDS. The results show that these nanowires are very uniform with the diameter of 100 nm. The observed coercivity (HC) and squareness (Mr/Ms) of CoNiP single nanowires are larger than the CoNiP/Au multisegment nanowires.